A Market Model of Eastern Bering Sea Alaska Pollock: Sensitivity to Fluctuations in Catch and Some Consequences of the American Fisheries Act. (16th October 2014) - Strong, James W.; Criddle, Keith R.
Abstract: A simultaneous‐equation equilibrium model of domestic and international markets for fillets, surimi, and roe of Alaska pollock (i.e., Walleye Pollock Gadus chalcogrammus ) is used to examine the combined effect of variability in landings and changes in product mix on first wholesale prices and revenues. From the commencement of Americanization in the mid‐1970s through the joint venture era of the 1980s and following full Americanization in early 1990s, U.S. producers of Alaska pollock focused mainly on selling surimi and roe to Japan. Passage of the American Fisheries Act of 1998 (AFA) unleashed an economic transformation that more than doubled fishery revenues without increasing exploitation rates or catches. The increased value came about because freedom from the race for fish allowed fishers and processors to increase product quality, improve product recovery rates, diversify their mix of product forms, and develop new markets in the USA and Europe. Despite the size and importance of the Alaska pollock fishery—among U.S. fisheries, it consistently ranks number one by volume and in the top five by value—little attention has been given to the development of a formal model of Alaska pollock markets or the market impacts of the AFA. The results of the model indicate that first wholesale revenues are maximized when harvests are maximized, but the value of the harvest is particularly sensitive to changes in the demand for Alaska pollock harvested in Russian waters, price differentials between fillet and surimi, and Japanese inventories of Alaska pollock products. Comparative static simulations comparing pre‐ and post‐AFA fishery product recovery rates and product mix indicate revenues would have increased by 62% from 1998 to 2007. Received June 21, 2013; accepted July 1, 2014